Let $a,b,c$ denote rational numbers, such that $(a+b\sqrt[3]2+c\sqrt[3]4)^3$ is also rational. Prove that at least two of the numbers $a,b,c$ must be zero. Actually I confused of the beginning steps for this proof. Should I apply the strategies of contradictory proofs

  • 2
    $\begingroup$ First expand the expression. Notice that the product of a non zero rational number with an irrational number is an irrational number. Also notice that $\sqrt[3]{2}$ and $\sqrt[3]{4}$ are irrational numbers. $\endgroup$ – Scientifica Jul 18 '14 at 16:27

Since $$(a+bx+cx^2)^3\equiv (6bc^2+3a^2c+3ab^2)x^2+(6ac^2+6b^2c+3a^2b)x+(4c^3+2b^3+a^3+12abc)\pmod{(x^3-2)}$$ if $(a+b\sqrt[3]{2}+c\sqrt[3]{2})^3$ belongs to $\mathbb{Q}$ then $$(2bc^2+a^2c+ab^2)=0, \qquad (2ac^2+2b^2c+a^2b)=0,\tag{1}$$ hence: $$ a^2 b^2 c^2 = (a^2c+ab^2)(ac^2+b^2 c) = a^3 c^3 + 2a^2 b^2 c^2 + ab^4 c,$$ $$ a^3 c^3 + a^2 b^2 c^2 + ab^4 c = 0,$$ $$ ac (a^2 c^2 + a c b^2 + b^4) = 0.$$ Since the discriminant of $y^2+y+1$ is negative, the last equation implies $a=0$ or $c=0$. If we plug this identities back into $(1)$, we get that the only possibilities are that at least two variables among $\{a,b,c\}$ are zero.


Oh an answer while I was writing! (I was writing in Notepad not directly in the forum).

Anyway, before answering the question, lets prove these:

Lemma 1: $\sqrt[3]{2}\not\in\mathbb{Q}^+$.

Corollary: $\sqrt[3]{4}\not\in\mathbb{Q}^+$.

Lemma 2: $\forall (a,b)\in\mathbb{Z}^2,\,a\sqrt[3]{2}+b\sqrt[3]{4}\in\mathbb{Q}\Longleftrightarrow (a,b)=(0,0)$

Theorem: $\forall (a,b)\in\mathbb{Q}^2,\,a\sqrt[3]{2}+b\sqrt[3]{4}\in\mathbb{Q}\Longleftrightarrow (a,b)=(0,0)$

Proof of lemma 1:

Assume that $\sqrt[3]{2}\in\mathbb{Q}$. Then $\exists !(a,b)\in\mathbb{N}^2,\,\sqrt[3]{2}=\dfrac{a}{b}$ such as $a,b\neq 0$ and $a∧b=1$.

Then $$a^3=2b^3\,\,\,\,(1)$$and so $a$ is an even number. Then $\exists k\in\mathbb{N},\,a=2k$ and so in $(1)$ we have $b^3=4k^3$ and so $b$ is also an even number which contradicts $a∧b=1$.

Proof of the corollary:

Assume that $\sqrt[3]{4}\in\mathbb{Q}^+$. Then $\sqrt[3]{4^2}\in\mathbb{Q}^+$ and so $2\sqrt[3]{2}\in\mathbb{Q}^+$ which contradicts the lemma 1.

Proof of lemma 2:

If $(a,b)=(0,0)$ then $a\sqrt[3]{2}+b\sqrt[3]{4}=0\in\mathbb{Q}$.

Now lets prove that $\forall (a,b)\in\mathbb{Z}^2,\,a\sqrt[3]{2}+b\sqrt[3]{4}\in\mathbb{Q}\Longrightarrow (a,b)=(0,0)$.

To prove it, lets prove that $\forall (a,b)\in\mathbb{Z}^2,\,(a,b)\neq (0,0)\Longrightarrow a\sqrt[3]{2}+b\sqrt[3]{4}\not\in\mathbb{Q}$

If $a=0$, and so $b\neq 0$, or $b=0$ and so $a\neq 0$, it's trivial that $a\sqrt[3]{2}+b\sqrt[3]{4}\not\in\mathbb{Q}$ using the lemma 1 or the corollary.

Assume that $\exists (a,b)\in\mathbb{Z}^2$ such as $a,b\neq 0$ and: $$a\sqrt[3]{2}+b\sqrt[3]{4}\in\mathbb{Q}\,\,\,\, (2.1)$$

Then $(a\sqrt[3]{2}+b\sqrt[3]{4})^2\in\mathbb{Q}$ and $(a\sqrt[3]{2}+b\sqrt[3]{4})^2=a^2\sqrt[3]{4}+2b^2\sqrt[3]{2}+4ab$.

While $4ab\in\mathbb{N}$ then: $$a^2\sqrt[3]{4}+2b^2\sqrt[3]{2}\in\mathbb{Q}\,\,\,\, (2.2)$$

By $(2.2)-\dfrac{a^2}{b}(2.1)\in\mathbb{Q}\,\,\,\,\left(\dfrac{a^2}{b}\in\mathbb{Q}^+\right)$ we get: $$\left( 2b^2-\dfrac{a^3}{b}\right)\sqrt[3]{2}\in\mathbb{Q}\,\,\,\, (2.3)$$

If $\left( 2b^2-\dfrac{a^3}{b}\right) =0$ then $a=\sqrt[3]{2}b\not\in\mathbb{N}$ which is false.

And so $\left( 2b^2-\dfrac{a^3}{b}\right)\neq 0$, but while $\left( 2b^2-\dfrac{a^3}{b}\right)\in\mathbb{Q}$ it means using $(2.3)$ that $\sqrt[3]{2}\in\mathbb{Q}$ which contradicts the lemma 1.

We conclude that $\forall (a,b)\in\mathbb{Z}^2,\,(a,b)\neq (0,0)\Longrightarrow a\sqrt[3]{2}+b\sqrt[3]{4}\not\in\mathbb{Q}$ which proves lemma 2.

Proof of the theorem:

If $(a,b)=(0,0)$ it's as same as in lemma 2.

Let $(a,b)\in\mathbb{Q}$ such as $a\sqrt[3]{2}+b\sqrt[3]{4}\in\mathbb{Q}$.

$(a,b)\in\mathbb{Q}$ so $\exists ((p,p'),(q,q'))\in\mathbb{Z}^2\times\mathbb{N}^{+2}\, (a,b)=\left(\dfrac{p}{q},\dfrac{p'}{q'}\right)$.

We have then:$$\dfrac{p}{q}\sqrt[3]{2}+\dfrac{p'}{q'}\sqrt[3]{4}\in\mathbb{Q}\,\,\,\, (3)$$

By $qq'\times (3)$ still $qq'\in\mathbb{N}^+$ we get $pq'\sqrt[3]{2}+p'q\sqrt[3]{4}\in\mathbb{Q}$. Using lemma 2 we get $(pq',p'q)=(0,0)$ and so $(p,p')=(0,0)$ and so $(a,b)=(0,0)$ which proves the theorem.

We know that: $$\forall (x,y,z)\in\mathbb{R}^3,\,(x+y+z)^3=x^3+y^3+z^3+3x^2(y+z)+3y^2(x+z)+3z^2(x+y)+6xyz\,(4)$$.

Now let $(a,b,c)\in\mathbb{Q}^3$ such as $(a+b\sqrt[3]{2}+C\sqrt[3]{4})^3\in\mathbb{Q}$.

By using $(4)$: $(a+b\sqrt[3]{2}+c\sqrt[3]{4})^3=a^3+2b^3+4c^3+12abc+3(a^2b+2b^2c+2ac^2)\sqrt[3]{2}+3(a^2c+ab^2+2bc^2)\sqrt[3]{4}$.

While $a^3+2b^3+4c^3+12abc\in\mathbb{Q}$, $(a+b\sqrt[3]{2}+C\sqrt[3]{4})^3\in\mathbb{Q}$ if and only if $3(a^2b+2b^2c+2ac^2)\sqrt[3]{2}+3(a^2c+ab^2+2bc^2)\sqrt[3]{4}\in\mathbb{Q}$.

Using the theorem: $(a+b\sqrt[3]{2}+C\sqrt[3]{4})^3\in\mathbb{Q}$ if and only if $a^2c+ab^2+2bc^2=0$ and $a^2b+2b^2c+2ac^2=0$.

Then see Jack D'Aurizio's post.


Step #$1$:

  • $a+b\sqrt[3]{2}\neq0 \implies c\notin\mathbb{Q}$

  • $a+c\sqrt[3]{4}\neq0 \implies b\notin\mathbb{Q}$

  • $b\sqrt[3]{2}+c\sqrt[3]{4}\neq0 \implies a\notin\mathbb{Q}$

Step #$2$:

  • $a+b\sqrt[3]{2}=0 \wedge a\neq0 \implies b\notin\mathbb{Q}$

  • $a+c\sqrt[3]{4}=0 \wedge a\neq0 \implies c\notin\mathbb{Q}$

  • $b\sqrt[3]{2}+c\sqrt[3]{4}=0 \wedge b\neq0 \implies c\notin\mathbb{Q}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.